FEATURES OF TEACHING ENGLISH ITSELF IN THE DEVELOPMENT OF PROFESSIONAL COMPETENCIES OF STUDENTS IN THE VETERINARY DIRECTION (World Bulletin of Public Health, 2024)
This article is devoted to the identification of strategies for using specific features in teaching English, as well as to the establishment of methods for demonstrating the professional psychological potential of veterinary students on the basis of English. The article covers the current issues of the use of pedtechnologiai in teaching English to students of Veterinary Specialty in the educational process and the effective performance of classes to what extent the teacher can Interest students and get them knowledge.
Keywords: development of the pharmaceutical network; integration; sociolinguistic competence